Environmentally Friendly Nafion-Mediated Friedländer Quinoline Synthesis under Microwave Irradiation: Application to One-Pot Synthesis of Substituted Quinolinyl Chalcones - Chan, Chieh-Kai; Lai, Chien-Yu; Wang, Cheng-Chung (Synthesis, 2020)
An efficient and eco-friendly synthetic route for Friedländer quinoline synthesis of polysubstituted quinolines is described. This green chemical method starts from various 2-aminobenzophenones and mono- or dicarbonyl synthons and uses reusable Nafion NR50 material as a solid catalyst in ethanol under microwave irradiation. The protocol has a high generality of functional groups and provides the desired quinolines in good to excellent yields. Some structures were confirmed by single-crystal X-ray diffraction analysis.
Keywords: Friedländer reaction; Nafion catalyst; quinolines; chalcone; microwave irradiation